Short-term effects and economic burden of air pollutants on acute lower respiratory tract infections in children in Southwest China: a time-series study - Yi He; Wanyanhan Jiang; Xi Gao; Chengwei Lin; Jia Li; Lian Yang (BMC, 2023)
Abstract Background There are few studies on the effects of air pollutants on acute lower respiratory tract infections (ALRI) in children. Here, we investigated the relationship of fine particulate matter (PM2.5), inhalable particulate matter (PM10), sulfur dioxide (SO2), and nitrogen dioxide (NO2) with the daily number of hospitalizations for ALRI in children in Sichuan Province, China, and to estimate the economic burden of disease due to exposure to air pollutants. Methods We collected records of 192,079 cases of childhood ALRI hospitalization between January 1, 2017 and December 31, 2018 from nine municipal/prefecture medical institutions as well as the simultaneous meteorological and air pollution data from 183 monitoring sites in Sichuan Province. A time series-generalized additive model was used to analyze exposure responses and lagged effects while assessing the economic burden caused by air pollutant exposure after controlling for long-term trends, seasonality, day of the week, and meteorological factors. Results Our single-pollutant model shows that for each 10 μg/m3 increase in air pollutant concentration (1 μg/m3 for SO2), the effect estimates of PM2.5, PM10, SO2, and NO2 for pneumonia reached their maximum at lag4, lag010, lag010, and lag07, respectively, with relative risk (RR) values of 1.0064 (95% CI, 1.0004-1.0124), 1.0168(95% CI 1.0089-1.0248), 1.0278 (95% CI 1.0157-1.0400), and 1.0378 (95% CI, 1.0072-1.0692). By contrast, the effect estimates of PM2.5, PM10, SO2, and NO2 for bronchitis all reached their maximum at lag010, with RRs of 1.0133 (95% CI 1.0025-1.0242), 1.0161(95% CI 1.0085-1.0238), 1.0135 (95% CI 1.0025-1.0247), and 1.1133(95% CI 1.0739-1.1541). In addition, children aged 5-14 years were more vulnerable to air pollutants than those aged 0-4 years (p < 0.05). According to the World Health Organization's air quality guidelines, the number of ALRI hospitalizations attributed to PM2.5, PM10, and NO2 pollution during the study period was 7551, 10,151, and 7575, respectively, while the incurring economic burden was CNY 2847.06, 3827.27, and 2855.91 million. Conclusion This study shows that in Sichuan Province, elevated daily average concentrations of four air pollutants lead to increases in numbers of childhood ALRI hospitalizations and cause a serious economic burden.